2009
DOI: 10.1007/s00276-008-0458-7
|View full text |Cite
|
Sign up to set email alerts
|

Ultrasonographic evaluation and morphometric measurements of the suprascapular notch

Abstract: Suprascapular notch measurements and the visualization of the anatomical neighborhood, which may be beneficial for the suprascapular nerve blockade procedure, can be successfully performed by the use of high-frequency ultrasound imaging.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
33
1
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 42 publications
(37 citation statements)
references
References 16 publications
2
33
1
1
Order By: Relevance
“…To visualize the transverse scapular ligament, the probe would have to be almost in a straight coronal position. Yücesoy et al 5 had nicely demonstrated the image of the suprascapular notch and the transverse ligament. However, a slight deviation of the probe orientation from that position would result in scanning the floor of the suprascapular fossa.…”
Section: Discussionmentioning
confidence: 98%
See 3 more Smart Citations
“…To visualize the transverse scapular ligament, the probe would have to be almost in a straight coronal position. Yücesoy et al 5 had nicely demonstrated the image of the suprascapular notch and the transverse ligament. However, a slight deviation of the probe orientation from that position would result in scanning the floor of the suprascapular fossa.…”
Section: Discussionmentioning
confidence: 98%
“…[3][4][5] With the ultrasound probe placed in the suprascapular fossa in the long axis of the supraspinatus muscle, they described the visualization of the suprascapular notch, the transverse Based on the understanding of the anatomy of the scapula and our findings from the fluoroscopy image and cadaveric dissection, we would like to revisit the orientation of the ultrasound probe described by those authors as well as the interpretation of the findings of ultrasound images. Gofled 3 and Harmon 4 described the orientation of the probe as being ''parallel to the scapular spine''.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The size and shape of the SSN may be a factor in suprascapular nerve entrapment because narrow SSNs have been found in patients with this syndrome. 14,15,16,17 .…”
Section: Introductionmentioning
confidence: 99%